Analisis Gender dalam Amalan Sogit Masyarakat Murut Tahol di daerah Nabawan, Sabah: Gender Analysis in Sogit Practice among Murut Tahol Community in the District of Nabawan, Sabah - Buntung, Mastinah; Ramli, Mohd Anuar (Online Journal of Research in Islamic Studies, 2019)
This article discusses about sogit or sanction which has practiced in Murut Tahol community in the district of Nabawan, Sabah. The aim of the study is to identify the gender issues in sogit practices among Murut Tahol community. To collect the data, methods of library research and interviews were carried out toward custom figures and elderly of Murut Tahol. The gathered data were analyzed inductively. The result of study shows there are several sanction in sogit practices illustrate the element of bias gender in Murut Tahol community.